Creative Teaching Models for the Innovative Faint of HeartReview of: <source>Exemplary College Science Teaching</source>; <person-group> <name name-style="western"> <surname>Yager</surname> <given-names>Robert E.</given-names> </name> </person-group> (ed); ( <year>2013</year>). <publisher-name>National Science Teachers Association Press</publisher-name>, <publisher-loc>Arlington, VA</publisher-loc>. <fpage>243</fpage> pages. - Deborah K. Anderson (American Society for Microbiology, 2014)
Review of: Exemplary College Science Teaching; Robert E. Yager (ed); (2013). National Science Teachers Association Press, Arlington, VA. 243 pages.